Strategy as Practice Research: Reflections on its Rationale, Approach, and Contributions - Prashantham, Shameen; Healey, Mark P. (Journal of management studies, 2022)
Strategy as practice (SAP) research has developed into an established area of study, and the Journal of Management Studies (JMS) has played an important role in this as a hospitable outlet, including via a foundational special issue in 2003. This article offers a bird's eye view of the domain and a ready source of relevant literature to both seasoned scholars and newcomers to this topic. We make three observations that reflect both the JMS thematic collection and the wider literature on SAP and help to shed light on some of the key tensions facing scholars who seek to develop a distinct body of research. First, in terms of the rationale for SAP research, this body of work has grappled with its framing as building upon, yet distinct from strategy process research, to delve into practices within strategy process. Second, in terms of the approach to research (and community‐building), SAP research has reflected European intellectual roots which has helped to deliver on its broad research purpose but has perhaps also impeded its impact on more mainstream strategy. Third, in terms of the contribution of SAP research, there has been a large volume of high quality work, appearing in well‐regarded journals, generating a considerable diversity of perspectives.